Differential ferrioxamine test for measuring chelatable body iron - Fielding, J. (1965)
The differential ferrioxamine test is a simple method for the measurement of chelation of body iron by desferrioxamine. A single six-hour specimen of urine is obtained after intravenous Desferal, accompanied by (59)Fe-ferrioxamine. Two values are measured: F(d), the excretion of ferrioxamine derived from body iron by chelation, and F(ex), the proportion of ferrioxamine excreted from a known intravenous dose. The data enables F(v), chelation of iron in vivo, to be calculated by simple proportion. Desferrioxamine chelation proceeds for about half an hour after injection. The results in normal subjects, in cases with known high iron stores, and in cases of iron-deficiency anaemia are described. High, normal, and low body iron states have been differentiated. F(v) values in the higher ranges obtained in iron-storage diseases and in haemolytic states are differentiated by the pattern of excretion, high F(d) values and low F(ex) values respectively. It is suggested that there are two main sources of chelatable body iron: as ferritin-haemosiderin and as iron newly released from haem in a more readily chelatable form. The significance of variable chelation susceptibility in iron metabolism is briefly discussed. It is suggested that variable chelatability of different sources of body iron may explain the preferential utilization of iron released from red cells or absorbed from the intestine, rather than storage iron, in the biosynthesis of haem.